Análisis cualitativo del nivel de pobreza y extrema pobreza en la zona centro, departamento de Junín. El caso de Pariahuanca - Ramírez Miranda, Ridberth (2009)
This investigation started from the premise that if it is true that poverty is as old as mankind, is the polar opposite of wealth, poverty depends on the relative development reached by particular region or country which is why there are so many definitions of poverty and how to measure it, as aspects or criteria existanl, which ha ve given rise to plans, programs and guidelines for the Fight poverty with little or nothing has allowed significant reduction of poverty especially in rural areas where people live in measured great potential expressed in capitals: human, natural, physical and social, which does not offer any kind of opportunity to initiate a process of sustainable human development, the question is why the rural population continues to live in the midst of widespread poverty, persistent and intergenerational, the same measures that constitute barriers to sustainable human development process that will enable them to lead a decent life?